2015
DOI: 10.1074/jbc.m114.582700
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Structural Characterization of the Interaction between the FMN Binding Domain of Cytochrome P450 Reductase and Cytochrome c

Abstract: Background: Cytochrome P450 reductase (CPR) is an electron donor for many proteins. Results: The FMN binding domain (FBD) of CPR interacts with cytochrome c transiently and reduces cytochrome c at a higher rate than CPR. Conclusion: A three-dimensional structural model of the FBD-cyt c complex is presented. Significance: The findings give insights into the domain motions and the function of CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…This suggests that cyt c does not bind to oxidized CPR and/ or that the interactions between these two proteins upon binding do not cause significant structural rearrangement of CPR. A recent NMR study of the interaction between the FMN domain of CPR and cyt c has demonstrated that transient dynamic complexes are formed between the two proteins [39]. Taken together, these data are consistent with a model whereby ET from CPR to cyt c occurs in a diffusion-controlled manner through formation of a collisional complex that does not require domain re-organization in CPR.…”
Section: Discussionsupporting
confidence: 81%
“…This suggests that cyt c does not bind to oxidized CPR and/ or that the interactions between these two proteins upon binding do not cause significant structural rearrangement of CPR. A recent NMR study of the interaction between the FMN domain of CPR and cyt c has demonstrated that transient dynamic complexes are formed between the two proteins [39]. Taken together, these data are consistent with a model whereby ET from CPR to cyt c occurs in a diffusion-controlled manner through formation of a collisional complex that does not require domain re-organization in CPR.…”
Section: Discussionsupporting
confidence: 81%
“…Cyt c is a component of the electron transfer chain in mitochondria required for the production of ATP. The heme group of cyt c performs electron transfer with membrane proteins bc1 complex and complex 4 47Fig. 5A.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few reports have appeared of structures of complexes [45, 107, 116] (Figure 6). Some NMR studies have been done to identify parts of proteins involved in complexation [104, 117], but many questions still remain, as discussed under the description of P450 17A1.…”
Section: Future Needs In P450 Structural Workmentioning
confidence: 99%